Sugar-sweetened beverage intake and anthropometric profile of grade 6 learners in the Nelson Mandela Bay area, South Africa: a mixed-methods study - Stansbury, Candice; Ebrahim, Zarina; Nel, Daniel; Love, Penelope; Smit, Yolande (The South African journal of clinical nutrition, 2025)
Background A paucity of data exists regarding the intake of sugar-sweetened beverages (SSBs) among children and the prevalence of childhood overweight and obesity in the Nelson Mandela Bay area in South Africa (SA). Objective To obtain anthropometric data (weight and height), describe the SSB intake, and explore perceptions regarding SSBs of Grade 6 learners attending quintile four and five public schools in the Nelson Mandela Bay (NMB) area. Design A mixed-method study with a convergent design was employed. The quantitative phase was a cross-sectional descriptive study with an analytical component. The qualitative phase followed a phenomenological approach. Setting Quintile 4 and 5 public schools in the NMB area. Subjects Grade 6 learners. Outcomes measured A self-administered questionnaire and focus-group discussions (FGDs) provided information on SSB intake and perceptions regarding SSBs. The anthropometric profile of learners was described. Results A total of 183 learners completed the questionnaire, of which 24.6% and 16.4% were classified as overweight and obese respectively. Soft drinks were the most consumed SSB, with 77.6% of learners reporting a frequency of one to four times per week. There was no statically significant relationship between BMI and SSB intake. There was a statistically significant positive relationship between sugar-free drinks (p = 0.019) and BMI. Learners had a high awareness of the negative health effects of SSBs, but this did not deter them from consuming SSBs. Conclusion A multi-sectoral approach including advocating for policy reform and the Health Promotion Levy, coupled with parent education, is recommended to reduce SSB consumption in children to curb childhood overweight and obesity in SA.